2020
DOI: 10.31983/keslingmas.v39i2.4597
|View full text |Cite
|
Sign up to set email alerts
|

Surveilans Pengawasan Air Bersih Dan Limbah Cair Rumah Sakit Umum Hidayah Purwokerto

Abstract: Rumah sakit sebagai sarana kesehatan tempat berkumpulnya orang sakit maupun orang sehat dan dapat menjadi tempat penularan penyakit serta memungkinkan terjadinya pencemaran lingkungan dan gangguan kesehatan. Kegiatan kesehatan lingkungan rumah sakit agar terpantau secara continue maka diperlukan salah satu kegiatan yaitu surveilans. tujuan dari penelitian ini adalah mengetahui surveilans pengawasan air bersih dan limbah cair di Rumah Sakit Umum Hidayah Purwokerto. Metode penelitian iniadalah observasional deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Penelitian Taek et al, (2018) dan Asanti et al, (2018) Dampak tersebut sampai saat ini masih menjadi sebuah masalah yang belum ditanggulangi oleh pihak rumah sakit. Hal ini diketahui karena sampai saat ini masih belum ada penelitian terbaru yang membahas mengenai pemecahan atau solusi dari masalah tersebut.…”
Section: Hasil Dan Pembahasan a Kualitas Kimia Air Bersihunclassified
“…Penelitian Taek et al, (2018) dan Asanti et al, (2018) Dampak tersebut sampai saat ini masih menjadi sebuah masalah yang belum ditanggulangi oleh pihak rumah sakit. Hal ini diketahui karena sampai saat ini masih belum ada penelitian terbaru yang membahas mengenai pemecahan atau solusi dari masalah tersebut.…”
Section: Hasil Dan Pembahasan a Kualitas Kimia Air Bersihunclassified
“…It can be concluded that the wastewater treatment process carried out at X Hospital South Sumatra has been going well, the waste produced has met the quality standards of hospital liquid waste, therefore it is safe to flow into water bodies and does not interfere with the health of the community around the hospital. The recording of the daily average wastewater discharge at the inlet and outlet tanks (Table 3) which were generated from several sources of liquid waste, the average waste discharge in June was 5.85 m 3 To anticipate the excess capacity of wastewater discharge that enters the WWTP tank, an indicator pipe has been prepared in the WWTP equipment carriage, where wastewater that exceeds the maximum discharge limit, will enter through the indicator pipe and flow back into the equalization tank and return to the initial stage of processing. This is different from the research by Ninggrum and Khalista (2014) which was conducted at X Jember Hospital, where waste water that exceeded the capacity of the holding tank was overcome by increasing the capacity of the bake rob reactor, you can also add a septic tank to accommodate waste from the bathroom.…”
Section: Wastewater Treatment Process At X Hospitalmentioning
confidence: 99%
“…The hospital is a health service institution that provides complete individual health services that provide inpatient, outpatient, and emergency room services [1] [2]. The hospital as a health service facility, a gathering place for sick and healthy people, or can be a place for disease transmission and allows environmental pollution and health problems [3]. Hospitals include producers of waste originating from medical and non-medical activities that have hazardous and toxic properties in large quantities and have a large impact on the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%